2018
DOI: 10.1021/acs.jafc.7b06038
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Physical Properties of Ethylcellulose/Gelatin Composite Nanofibers by Electrospinning

Abstract: In this work, the ethylcellulose/gelatin blends at various weight ratios in water/ethanol/acetic acid solution were electrospun to fabricate nanofibers with tunable physical properties. The solution compatibility was predicted based on Hansen solubility parameters and evaluated by rheological measurements. The physical properties were characterized by scanning electron microscopy, porosity, differential scanning calorimetry, thermogravimetry, Fourier transform infrared spectroscopy, and water contact angle. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(27 citation statements)
references
References 43 publications
0
27
0
Order By: Relevance
“…Electrospinning PVA/gelatine blends was used to create scaffolds with modifi ed hydrophobicity and morphology [11]. Similar results were found in ethyl cellulose/ gelatine blends, which could be tailored between hydrophobic and hydrophilic properties, showing tuneable water stability [12]. Zein/gelatine blends were found to show high crystallinity, resulting in the preservation of a porous 3D structure gained by electrospinning, which was not possible in pure gelatine or pure zein nanofi bers [13].…”
Section: Izvlečekmentioning
confidence: 70%
“…Electrospinning PVA/gelatine blends was used to create scaffolds with modifi ed hydrophobicity and morphology [11]. Similar results were found in ethyl cellulose/ gelatine blends, which could be tailored between hydrophobic and hydrophilic properties, showing tuneable water stability [12]. Zein/gelatine blends were found to show high crystallinity, resulting in the preservation of a porous 3D structure gained by electrospinning, which was not possible in pure gelatine or pure zein nanofi bers [13].…”
Section: Izvlečekmentioning
confidence: 70%
“…Therefore, it plays an important part in cell attachment, growth, migration and differentiation, as well as the formation of new tissues [10,11,12]. Meanwhile, gelatin fibers have strong adsorption, good filtration, barriers, adhesion and hygroscopicity [13,14,15,16]. Therefore, the gelatin 3D nanostructures prepared by electrospinning can be widely used in the biomedical materials, which receives more and more attention.…”
Section: Introductionmentioning
confidence: 99%
“…The water contact angle of CA/Gel and CA/Gel/Beri nanofibers were 58.07 ± 2.35° and 56.93 ± 1°, respectively, which indicated that the fabricated dressings are hydrophilic and proper for absorbing exudates and maintaining the moisture of the wound bed. Liu et al 54 demonstrated that the incorporation of Gel could increase the surface wettability of cellulose acetate due to its hydrophilic nature.…”
Section: Fabricatedmentioning
confidence: 99%